Maximal operator in total Morrey-Guliyev spaces defined on Carleson curves - Celik, Suleyman (Institute of Mathematics and Mechanics, National Academy of Sciences of Azerbaijan, 2026)
In this paper we study the maximal operator MΓ in the total Morrey-Guliyev space Lp,λ,µ(Γ) defined on Carleson curves Γ. We prove that for 1 < p < ∞ the maximal operator MΓ is bounded on the total Morrey-Guliyev space Mp,λ,µ(Γ), and from the total Morrey-Guliyev space M1,λ,µ(Γ) to WL1,λ,µ(Γ). © (2026), (GENERAL), All Rights Reserved.
Keywords: Carleson Curves; Modified Morrey Spaces; Morrey Spaces; Total Morrey-Guliyev Spaces